Reducing the Intergenerational Conflict between Generation Y and Generation Z through Creating a Culture of Mutual Respect - Bukhari, Sadia; Nadeem, Dr. Muhammadi Sabra (UW Journal of Management Sciences, 2024)
Purpose: The purpose of the study is to understand the Intergenerational conflict between Generation Y and Z which arises among them due to differences in their work values. This study also helps to determine the impact of creating a culture of mutual respect to reduce generational conflict. Methodology: The data of the study was collected from Higher Education Commission in the form of dyads. These dyads were representing Generation Y as supervisor and Generation Z as subordinates. The data was collected in a non-dyadic method (separate interviews were conducted with supervisors and subordinates). The purposive sampling technique was used with two criteria i.e. Organizational Structure and Age. Ten interviews were conducted with the respondents which were classified into four dyads. For analysis, Framework Metrix Method was used in the Nvivo 14. Findings: The results of the study indicate that generational conflict exists between Generation Y and Z due to differences in their working values and a culture of mutual respect plays a positive role in curbing this conflict. The Thematic Analysis was performed by using Framework Metrix Method to identify the main and sub themes. The three main themes represented some overlaps and contrast in the summarized data of dyads. The maximum overlap is observed between Generation Y and Z in the sub themes of ‘Fostering a Culture of Mutual Respect’. Implication: The maximum age of generation Z is 27 years, and they are entering into Pakistani workforce. Hence, this study may provide useful comprehensions to the organizational leaders to handle the young generation.